Science Teachers’ Attitudes Towards Internal Assessment System at The Secondary Level - Ghimire, Paras Mani; Panday, Jagat Prasad (Ganeshman Darpan, 2025)
Science Teachers' Attitudes Towards Internal Assessment System at The Secondary Level attempts to find out attitude of teachers towards the Internal (formative) assessment (FA) system in secondary level science classroom in surkhet district. For this study, forty-one secondary level science teachers of surkhet district were selected through random sampling procedure. After selecting the respondent, the questionnaires with five points Linkert Scale to study attitude of respondent on FA including their perception, experience and belief about FA was constructed with the helps of expert and send to each respondent through online. The major findings of the study show that teacher had positive attitude in practice of formative assessment system in secondary level science classroom despite there were several difficulties faced by science teacher during implementation of FA in classroom such as time & effort consuming, costly, resisted by student, lack of resources & technology, varying level and prior knowledge of student etc. This study also concludes that, almost all teacher of secondary level either often or always or sometime used at least one formative assessment tool among observation, open-ended question, close-ended question, peer feedback, think –pair share, quizzes, self-assessment and concept mapping in their classroom. Thus, it this study concluded that, in secondary level schools of surkhet district science teacher were implementing FA tools successfully even there were a lot of challenges for implementing it in science classroom.